1989
DOI: 10.1051/alr:1989005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the male reproductive tract in seven families of South-American catfishes

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
86
0
10

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 8 publications
6
86
0
10
Order By: Relevance
“…Some families of the order Siluriformes that present fringed testis show secretory activity at their caudal portions, sometimes having a seminal vesicle (LOIR et al 1989). The caudal fringes of the maturing testis of L. alexandri presented tubules internally coated by prismatic, secretory cells, with their lumen filled by secretion and spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Some families of the order Siluriformes that present fringed testis show secretory activity at their caudal portions, sometimes having a seminal vesicle (LOIR et al 1989). The caudal fringes of the maturing testis of L. alexandri presented tubules internally coated by prismatic, secretory cells, with their lumen filled by secretion and spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…In the caudal portion of the maturing / mature testes of L. lentiginosa, secretory tissue was observed, which produced an acidophilus secretion but did not form an individualized glandule. However, LOIR et al (1989) observed a non-defined seminal vesicle in the caudal region of the testes Hypostomus gymnorhynchus (Norman, 1926); Pseudoancistrus barbatus (Valenciennes, 1840) and Harttia surinamensis (Beseman, 1971) from the family Loricariidae.…”
Section: Discussionmentioning
confidence: 99%
“…In most fish species gonads are paired organs of similar size, which can be partially or totally fused (LE GAC & LOIR 1999). Some Siluriformes fishes from families Pimelodidae, Loricariidae and Callichthyidae present secretory activity in the caudal portion of the testes, sometimes forming a seminal vesicle (LOIR et al 1989).…”
mentioning
confidence: 99%
“…17a-c;Ihering, 1937;Britski, 1972;Loir, 1989;Royero, 1999: #120;Akama, 2004: #142). However, some auchenipterids, including Auchenipterichthys, Glanidium, Liosomadoras, Pseudauchenipterus, Pseudepapterus, Tetranematichthys, Tocantinsia, Trachelyichthys, Trachelyopterichthys, Trachelyopterus, and Trachycorystes, have the posterior testicular lobes modified into storage bags (Figs.…”
mentioning
confidence: 99%